Penerapan Algoritma Electre Sebagai Pendukung Keputusan Kasus Pengangkatan Guru Tetap - Fuad, Evans; Lysa Susticha; Desti Mualfah (Department of Information System Muhammadiyah University of Riau, 2021)
Assessment, evaluation and awarding can be carried out aimed at spurring the performance of teachers in the teaching and learning process so as to improve teacher achievement, the assessment is carried out to obtain honorary teachers who excel who will then be appointed as permanent teachers. The mechanism for appointing permanent teachers at the Muhammadiyah 3 Pekanbaru foundation, namely the Principal submits a list of names of teachers who will be recommended to be appointed as permanent teachers for thefoundation to the Head of PDM Education and Culture Pekanbaru City. The evaluation process for the appointment of permanent teachers at the foundation takes a very long time, then when checking and giving a value to the form provided with this process, itis feared that there will be a subjective assessment or the possibility of errors in writing numbers. The assessment criteria applied to the appointment of permanent teachers consist of years of service, PKP value, achievement, age. The author builds a decision support system using the Elimination and Choice Translation Reality method. In an effort to objectively determine to become a permanent teacher, this selection of permanent teachers will be very useful in motivating teachers to work well.